Improving the quality of learning through strengthening the lesson study community based on "Competition exploration" - Winaryati, Eny; Safuan, S.; Mulyadi, Dodi; Hasan, Muthia; Wijanarko, Nurunnisa Hanif; Maulana, Feri Reiza; Ivana, Marvina Irma; Anam, Moch. Khoirul (Journal of Community Service and Empowerment, 2022)
Key Performance Indicators no. 7 provide direction for the application of problem-solving learning methods, and recommend implementing project-based group learning (team-based projects). Implementation of collaborative learning activities can be carried out through the Lesson Study for Learning Community method. Collaboratively, all existing LS teams carry out planning, observation, and reflection. This activity was aimed to analyze the improvement of the quality of collaborative learning in lesson study communities in Muhammadiyah schools throughout Central Java based on "Competition Exploration". Implementation of activities in the field begins with Lesson Study workshops, learning models, writing scientific articles and IPR. In order to strengthen the article writing skills for teachers of the Lesson Study Team at Muhammadiyah schools throughout Central Java, this community service activity was followed up with a safari in 6 residencies in Central Java. The activity emphasizes assisting in writing scientific articles and submitting IPRs. From this assistance, 40 scientific articles and 40 HKI proposals, 40 lesson designs, and learning videos were produced. The community service team has produced 1 scientific article in the field of service, and 18 news articles in the mass media. Thus, this activity was successfully implemented and there was an increase in the quality of collaborative learning in the lesson study community.